Apuntes sobre prácticas y teorías mayas de relación - Grecco Pacheco, Daniel (2026)
The act of existing presupposes a relational practice, a constant being-in-the-world, which defines existence and allows knowledge and philosophies to emerge. This article aims to explore the relational character of Maya ontologies of different temporalities and contexts, with a reflection about the relations that define the existence, memory, and identity of Maya groups, establishing a bridge between different temporalities, in which past, present and future intertwine and cohabit in modes of omnipresence. Starting with a movement of listening from within to the wisdoms of contemporary Maya communities, I will discuss different cases that make explicit the fundamental nature of the experience of relation for life and the formation of beings. Through the cases discussed throughout this article, it will be possible to sentipensar about how relational practices constitute the foundations of Maya ontologies of different temporalities and spaces. The Maya being is constructed from a permanent movement of contact with other human and more-than-human beings, landscapes, and other temporalities.